Virological surveillance of bats in Southern Kazakhstan - Karamendin, Kobey; Sabyrzhan, Temirlan; Kydyrmanov, Aidyn; Kasymbekov, Yermukhammet; Khan, Yelizaveta; Nuralibekov, Sardor; Goodman, Simon J. (Frontiers in Virology, 2025)
Bats are known as an important natural reservoir of many viral infections, from which transmission into the human population occurs. This article aimed to examine bats in Kazakhstan for possible circulation of viruses dangerous to humans and other animals. Two hundred sixty samples, including nasal and rectal swabs and blood sera, were collected from bats in southern Kazakhstan. Studies of the bat virome applying high-throughput sequencing revealed the presence of five large families: Circoviridae, Parvoviridae, Retroviridae, Adenoviridae, and Orthoherpesviridae. All of them were found in southern Kazakhstan from Myotis blythii adult individuals of both sexes. Genomic studies of bat herpesviruses have shown that they are potentially representatives of novel species, genetically different from existing ones. Their epidemic potential for humans and other animals requires further research. Serological studies for possible circulation of antibodies to coronaviruses and influenza A viruses have shown negative results, indicating the absence of antibodies in the tested samples. The results demonstrate the need for more profound research to identify the relationship between human and bat viruses in the future.